TINGKAT KECUKUPAN ZAT GIZI DAN CAIRAN, KUALITAS DIET, AKSES PANGAN SERTA AKTIVITAS FISIK DAN STATUS GIZI PENGENDARA OJEK ONLINE TANGERANG - Nurhayati, Arin Fransisca; Palupi, Khairizka Citra; Mulyani, Erry Yudhya; Ronitawati, Putri; Sitoayu, Laras; Sapa'ang, Mertien (Journal of Nutrition College, 2024)
ABSTRACTBackground: Online motorcycle taxi drivers are one of the alternative jobs Indonesian demand with 4 million online motorcycle taxi drivers currently spread throughout Indonesia. Workers from the transportation industry also present high health problems due to overweight and obesity. Several factors can affect the nutritional status of the workforce, such as the type of activity (workload), individual labor factors (gender, age, physiological status, fitness level, and eating habits), as well as factors from the work environment (including: physical, chemical, biological, physiological, psychological science and ergonomics). Therefore, the nutritional status of online motorcycle taxis is one of the things that needs attention. Objectives: Analyze the relationship between the adequacy of nutrients and fluids, diet quality, consumption behavior and physical activity with the nutritional status of online ojek drivers in Tangerang. Methods: This study used a Cross Sectional study design. The sample size in this study was calculated using G*Power software, namely 92 samples selected by the non-probability sampling method by accidental sampling. Data on respondents' characteristics and consumption behavior were obtained from questionnaires, the level of adequacy of nutrients and fluids was obtained from the results of recall 1x24 hours for two days, diet quality was assessed from the Balanced Nutrition Index score (IGS 3-60), physical activity was calculated using the PAL form 1x24 hours. Nutritional status was obtained from anthropometric measurements. The data obtained were processed using the Pearson Chi-Square test. Results: There was a significant relationship between the level of adequacy of energy, carbohydrates, fat, frequency of buying food outside and nutritional status (P-value 0.000; 0.000; 0.041; 0.047). There was no significant association between protein adequacy, fiber adequacy, fluids, diet quality, physical activity, cooking frequency and delivery frequency with nutritional status (P-value 0.636; 0.489; 0.556; 0.282; 1.00; 0.056; 0.617).Conclusion: There was a relationship between the level of adequacy of energy, carbohydrates, fat, and the frequency of buying food outside with nutritional status and there was no relationship between the level of adequacy of protein, fiber, fluids, diet quality, physical activity, cooking frequency and frequency of delivery with nutritional status.Keywords: diet quality; food access; level of adequacy of nutrients and fluids; nutritional status; online motorcycle taxi; physical activity ABSTRAKLatar belakang: Pengendara ojek online merupakan salah satu alternatif pekerjaan yang diminati masyarakat Indonesia dengan 4 juta pengendara ojek online saat ini yang tersebar di seluruh Indonesia. Pekerja dari industri transportasi juga menyajikan permasalahan kesehatan yang tinggi karena kelebihan berat badan dan obesitas. Oleh karena itu, status gizi ojek online menjadi salah satu hal yang perlu diperhatikan. Tujuan: menganalisis hubungan tingkat kecukupan zat gizi dan cairan, kualitas diet, perilaku konsumsi serta aktivitas fisik dengan status gizi pengendara ojek online Tangerang. Metode: Penelitian ini menggunakan desain studi Cross Sectional (potong lintang). Besar sampel pada penelitian ini dihitung menggunakan software G*Power yaitu 92 sampel yang dipilih dengan metode non probability sampling dengan cara accidental sampling. Data karakteristik responden dan perilaku konsumsi diperoleh dari kuesioner, tingkat kecukupan zat gizi dan cairan diperoleh dari hasil recall 1x24 jam selama 2 hari, kualitas diet dinilai dari skor Indeks Gizi Seimbang (IGS 3-60), aktivitas fisik dihitung menggunakan form PAL 1x24 jam serta status gizi diperoleh dari pengukuran antropometri. Data yang diperoleh diolah menggunakan uji Chi-Square. Hasil: Terdapat hubungan signifikan antara tingkat kecukupan energi, karbohidrat, lemak, frekuensi membeli makanan di luar dengan status gizi (p value 0,000; 0,000; 0,041; 0,047). Tidak terdapat hubungan signifikan antara tingkat kecukupan protein, tingkat kecukupan serat, cairan, kualitas diet, aktivitas fisik, frekuensi memasak dan frekuensi pesan antar dengan status gizi (p value 0,636; 0,489; 0,556; 0,282; 1,00; 0,056; 0,617). Kesimpulan: Ada hubungan antara tingkat kecukupan energi, karbohidrat, lemak, dan frekuensi membeli makanan di luar dengan status gizi. Tidak ada hubungan antara tingkat kecukupan protein, serat, cairan, kualitas diet, aktivitas fisik, frekuensi memasak dan frekuensi pesan antar dengan status gizi.Kata Kunci: akses pangan; aktivitas fisik; kualitas diet; ojek online; status gizi; tingkat kecukupan zat gizi dan cairan